Multiwavelength follow-up observations of the tidal disruption event candidate 2XMMi J184725.1−631724. Issue 3 (16th November 2017) - Lin, Dacheng; Strader, Jay; Carrasco, Eleazar R; Godet, Olivier; Grupe, Dirk; Webb, Natalie A; Barret, Didier; Irwin, Jimmy A
Abstract: The ultrasoft X-ray flare 2XMMi J184725.1−631724 was serendipitously detected in two XMM–Newton observations in 2006 and 2007, with a peak luminosity of 6 × 10 43  erg s −1 . It was suggested to be a tidal disruption event (TDE) because its position is consistent with the centre of an inactive galaxy. It is the only known X-ray TDE candidate whose X-ray spectra showed evidence of a weak steep power-law component besides a dominant supersoft thermal disc. We have carried out multiwavelength follow-up observations of the event. Multiple X-ray monitorings show that the X-ray luminosity has decayed significantly after 2011. Especially, in our deep Chandra observation in 2013, we detected a very faint counterpart that supports the nuclear origin of 2XMMi J184725.1−631724 but had an X-ray flux a factor of ∼1000 lower than in the peak of the event. Compared with follow-up ultraviolet (UV) observations, we found that there might be some enhanced UV emission associated with the TDE in the first XMM–Newton observation. We also obtained a high-quality UV-optical spectrum with the Southern Astrophysical Research (SOAR) Telescope and put a very tight constraint on the persistent nuclear activity, with a persistent X-ray luminosity expected to be lower than the peak of the flare by a factor of >2700. Therefore, our multiwavelength follow-up observations strongly support the TDE explanation of the event.